O papel do Supremo Tribunal Federal no sistema de justiça penal e a teoria dos precedentes obrigatórios: uma análise comparada com a Suprema Corte dos Estados Unidos da América. - Mendonça, Jorge André de Carvalho (2019)
Concerned with the problem of different and random judicial decision-making processes for similar cases, especially concerning the failure of the Brazilian Supreme Court to comply with many axioms of the doctrine of binding precedents, when solving important criminal cases for the whole country, we first ask the reason why the justices act that way. The hypothesis inquired to answer this research question is based on the statement made by a group of Brazilian law professors, who are saying that it happens because the Brazilian court works as court focused on individual justice, rather than making the same law for everybody. Then, we have a second research question, asking how the Brazilian Supreme Court should behave to further accomplish its own precedents in the criminal field. We work in this second part with the assumption, based once more on the same group of law professors, that the national court needs to change its status from a “court of justice” to a “court of precedents”, becoming similar to the United States Supreme Court. To study the two hypothesis, we mainly analyze the data from both courts, as well as some important criminal cases solved by them. We confirm a tendency for the Brazilian court to work as a “court of justice”, but taking into account only the decisions made in important criminal cases. Taking into consideration only our qualitative approach, we realize that it is neither making criminal law for the future nor unifying it for the whole country. Nevertheless, we also realize that a quantitative approach, in addition to the qualitative one, although not feasible for us, may lead to an opposite conclusion, especially if it takes a big sample of the large number of routine cases, solved by the Brazilian court by simple reproduction. Moreover, we cannot confirm the second hypothesis, because the claim that the Supreme Court of the United States works as a court of precedent is also very doubtful. Like the Brazilian one, on many occasions it neither makes laws for the future, nor standardizes most cases solved in different ways by lower courts. Actually, because of its discretionary option to solve the cases or not, it seems to work closer to a “court of management justice” system, focused on solving, by its own subjective criteria, only what it thinks is very important to the United States.